Patient-centered outcomes: a qualitative exploration of patient experience with electroencephalograms in the Emergency Department - Christine S. Davis; Sandra K. Beverly, MD; Jackeline Hernandez-Nino; Andrew J. Wyman; Andrew W. Asimos (Qualitative Research in Medicine & Healthcare)
The primary objective of this qualitative project was to understand the experience of patients who had first-time seizures and who did, and did not, have electroencephalograms (EEGs) performed in the Emergency Department (ED) as part of their initial evaluation, so as to refine the diagnostic and therapeutic approach to these patients and transform the standard of care for first-time seizures by focusing on outcomes as defined by patient experiences and expectations. In this paper, we show that, regardless of the diagnostic and therapeutic approach patients are given in the ED, patients and caregivers trust that health care providers will perform the standard of care consistent with the current medical practice for first-time seizures. However, performing EEGs in the ED and initiating appropriate anticonvulsant therapy for those patients who are at high risk for future seizures addresses patient needs by offering patients a sense of security and control over their medical condition and expediting appropriate follow up care, as long as clearly stated written diagnostic, treatment, and referral instructions are provided upon discharge.